(untitled) (Physical Education, Health and Social Sciences, 2025)
Headache is one of the most common leading problems found in equal population. Moreover, about 90% of population is suffering from different types of headache. Similarly, Cervicogenic Headache (CGH) is a type of headache which is frequently found in students now-a-days due to forward neck posture associated with the symptoms of neck pain. In this research we are concluding if intensity of headache and neck pain decrease and cervical ROM increase after NAG mobilization and stretching in upper cervical region among students suffering from CGH. This study includes the comparison of two conservative treatments to reduce the intensity and frequency of CGH attacks are Mulligan’s NAG mobilization and stretching of neck muscles. Assessment of pain intensity and ROM of cervical spine done by VAS scale rating (0-10) and goniometry. Result conclusion shows significant positive results with mulligan in CGH.